2019
DOI: 10.24326/asphc.2019.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preharvest Deficit Irrigation Treatments in Combination With Reduced Nitrogen Fertilization on Orchard Performance of Nectarine With Emphasis on Postharvest Diseases and Pruning Weights

Abstract: Fruit production should be adapted to future scenarios that are frequently associated with scarce resources, especially freshwater and fertilizers. New biologically-based fruit production strategies, i.e. taking into account tree growth and water status, are required to optimize irrigation and fertilization under abiotic stress conditions. It was hypothesized that a moderate abiotic stress, here deficit irrigation with or without nitrogen deficit, in the preharvest period, could decrease postharvest losses due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Beyond woody crops, in Florida (USA) fresh market tomato production, severity of bacterial spot (Xanthomonas campestris) was not affected by deficit irrigation (70% and 85% ET versus 100% ET) (56); however, in this same study, early blight (Alternaria solani) was more severe under deficit irrigation (56). Generally, suppressive to neutral effects were hypothesized to be related to reduction in infectable plant tissue and suppression (or lack of an effect) on sporulation and infection under lower canopy humidity (5,6,56,84). In the unusual instance of increased disease severity under deficit irrigation, drought stress was postulated to compromise host resistance (56).…”
Section: How Changes In Irrigation Management Strategies Can Affect D...mentioning
confidence: 56%
See 1 more Smart Citation
“…Beyond woody crops, in Florida (USA) fresh market tomato production, severity of bacterial spot (Xanthomonas campestris) was not affected by deficit irrigation (70% and 85% ET versus 100% ET) (56); however, in this same study, early blight (Alternaria solani) was more severe under deficit irrigation (56). Generally, suppressive to neutral effects were hypothesized to be related to reduction in infectable plant tissue and suppression (or lack of an effect) on sporulation and infection under lower canopy humidity (5,6,56,84). In the unusual instance of increased disease severity under deficit irrigation, drought stress was postulated to compromise host resistance (56).…”
Section: How Changes In Irrigation Management Strategies Can Affect D...mentioning
confidence: 56%
“…In California almond orchards, Teviotdale et al (84) found that reducing water inputs to near-stress levels using deficit irrigation (in reference to base ET) reduced the incidence of dead leaf clusters, amount of dead wood, and incidence of hull rot caused by Rhizopus stolonifer and Monilinia fructicola. In nectarine orchards in Turkey, Atay et al (5) found that deficit irrigation up to 75% of full ET (drought stress-inducing) either suppressed or did not influence fruit rot development associated with species of Monilinia, Rhizopus, and Botrytis (species names not provided). Beyond woody crops, in Florida (USA) fresh market tomato production, severity of bacterial spot (Xanthomonas campestris) was not affected by deficit irrigation (70% and 85% ET versus 100% ET) (56); however, in this same study, early blight (Alternaria solani) was more severe under deficit irrigation (56).…”
Section: How Changes In Irrigation Management Strategies Can Affect D...mentioning
confidence: 99%